Sex galaxy - Davis, Mike; Phillips, Ben (Actor); Jenkins, Anthony (Actor); Swede, Puma, 1976- (Stag Films, 2008)
A hundred years into the future, global warming has turned the earth into a dust bowl. In order to combat the problem of overpopulation, all sexual congress has been outlawed. From Earth Station Central, 3 female-starved male astronauts are shot into space to fix a sewage problem on an outlying space station. After quickly fixing the plumbing, they decide to break the rules and fly on to a remote and mysterious planet. It is rumored that a tribe of beautiful Amazon women whose very existence is solely to satisfy men's desires inhabits the planet. On reaching their destination, the scientists discover that there are unexpected complications. --